Implementation of Policy Law Number 6 of 2014 in Improving The Effectiveness of Village Development - Maharani, Dewi (Budapest International Research and Critics University, 2021)
The purpose of this study is to empirically examine the policy of law number 6 of 2014 concerning villages. This law aims to improve the quality of life and life as much as possible to achieve the welfare of rural communities; in addition, this law reduces poverty levels by strengthening village development independently. This research method is quantitative, and the analytical technique used is path analysis. The data sources in this study were primary data and secondary data with data collection techniques through research questionnaires distributed to 64 respondents consisting of village officials and the Village Consultative Body (BPD). The study results indicate that the implementation of Law Number 6 of 2014 concerning Villages has been carried out well so that this has a positive influence on the effectiveness of village development carried out in the villages studied.